A systems approach to improving the quality of tree seedlings for agroforestry, tree farming and reforestation in the Philippines. (September 2015) - Gregorio, Nestor; Herbohn, John; Harrison, Steve; Smith, Carl
Highlights: We model causal relationships of factors affecting the supply of high quality seedlings. Improved quality of seedlings requires improving germplasm supply, skills of nursery operators and markets for seedlings. Government nurseries promote the effectiveness of overall nursery sector by producing species which cannot be supplied by other nursery groups. A systems approach allowed us to understand the complexity of factors influencing the quality of tree seedlings. Abstract: The limited supply of high quality planting materials for a wide species base is a major reason for the limited success of reforestation programmes or projects in many developing countries. This paper reports the research that was undertaken to improve the supply of high quality planting materials for agroforestry, tree farming and reforestation in the Philippines. A systems approach was used to identify mechanisms to improve the operational effectiveness of the forest nursery sector. A Bayesian Belief Network of the forest nursery sector was developed to examine the interactions between the key components of the forest nursery sector, identify key leverage points for intervention and explore potential impacts of possible policy interventions. Although improving the operational effectiveness of individual, communal and government nurseries will result in high operational effectiveness of the forest nursery sector, the operational effectiveness of government nurseries is likely to have a negative impact on the market for seedlings from smallholder nurseries i.e. individual and communal nurseries, thus impeding the sustainability of smallholder nurseries. Increasing the supply of high quality germplasm for a wide variety of species, improving the technical capabilities of smallholder nursery operators in seedling production and increasing the market demand of high quality seedlings from smallholder nurseries are the most important requirements for improving the operational effectiveness of the forest nursery sector. However, government nurseries can play a crucial role in improving the effectiveness of the forest nursery sector by diversifying their production to focus on species that are in demand by smallholder farmers and which cannot be supplied by individual or communal nurseries. Failing to do this will result in the current situation continuing in which government nursery sector competes with private and communal nurseries.